1983
DOI: 10.1037/0735-7028.14.4.435
|View full text |Cite
|
Sign up to set email alerts
|

The influence of confidentiality conditions on self-disclosure of early adolescents.

Abstract: The current study attempted to measure the effects of varying degrees of assurance of confidentiality on frequency of self-disclosure in a junior high school population. A selfdisclosure questionnaire was administered to 45 male and 45 female subjects. Male and female subjects were randomly divided into one of three treatment conditions: confidentiality explicitly assured, no instructions regarding confidentiality, and confidentiality explicitly not assured. A self-disclosure score was derived by summing the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Henry and Margaret are typical both of the general public and of many mandated professionals who assume that outside of suicide and or physical violence towards children, their statements in therapy are confidential. Many, if not most clients enter therapy with the expectation and misperception that everything they say will be held in the strictest confidence (Kobocow et al 1983). The burden of explaining confidentiality and limits to confidentiality falls directly to the clinician.…”
Section: Discussionmentioning
confidence: 98%
“…Henry and Margaret are typical both of the general public and of many mandated professionals who assume that outside of suicide and or physical violence towards children, their statements in therapy are confidential. Many, if not most clients enter therapy with the expectation and misperception that everything they say will be held in the strictest confidence (Kobocow et al 1983). The burden of explaining confidentiality and limits to confidentiality falls directly to the clinician.…”
Section: Discussionmentioning
confidence: 98%
“…Research has shown that patients who feel that their confidentiality is respected are more likely to seek treatment and comply with recommendations. [1][2][3][4][5][6][7][8][9][10][11][12][13] Our study, one of the few to enquire directly of patients about their views of medical confidentiality, suggests that while there is considerable overlap between professional and legal definitions and patient views, there are also important differences.…”
Section: Discussionmentioning
confidence: 99%
“…Findings suggest, for example, that patients who believe that their privacy will be respected are more likely to seek treatment, discuss problems openly, and return for follow up care. [1][2][3][4][5][6][7][8][9][10][11][12][13] In recognition of the importance of medical confidentiality to successful health outcomes, the US federal government recently adopted rules under the Health Insurance Portability and Accountability Act (HIPAA) to include the first comprehensive protection for the privacy of health information in the USA. 14 The primary purpose of the HIPAA privacy rule has been to direct the creation of a system of rules, practices, and oversight to protect medical information.…”
mentioning
confidence: 99%
“…A survey of Melbourne high school students found that 98% of adolescents believed that confidentiality within a school counselling setting was either essential or important (Collins & Knowles, ). It has also been shown that the number of disclosures regarding sensitive questions is higher when confidentiality is explicitly assured by psychologists (Kobocow, McGuire, & Blau, ). Findings about the importance of confidentiality for young people have also been demonstrated extensively in the field of adolescent medicine (Farrant & Watson, ; Ford, Millstein, Halpern‐Felsher, & Irwin, ; Jones, Purcell, Singh, & Finer, ; Reddy, Fleming, & Swain, ; Thrall et al., ).…”
Section: Empirical Research About Confidentiality In Psychological Prmentioning
confidence: 99%